Temporal and Spatial Hydrodynamic Variability in the Mallorca Channel (Western Mediterranean Sea) From 8 Years of Underwater Glider Data. Issue 4 (24th April 2019) - Barceló‐Llull, Bàrbara; Pascual, Ananda; Ruiz, Simón; Escudier, Romain; Torner, Marc; Tintoré, Joaquín
Abstract: Eight years of glider data are used to characterize the temporal and spatial variability of a region in the western Mediterranean that will constitute one of the targets for the calibration phase of the Surface Water and Ocean Topography (SWOT) satellite mission. The characteristic horizontal dimension of mesoscale instabilities in the Mallorca channel is 6.0 km. The temporal evolution of intermediate water masses is dominated by an increase over time of the characteristic temperature values. Western Mediterranean and Levantine Intermediate waters display an increase of the temperature extrema of 0.064 ± 0.002 and 0.044 ± 0.002 °C/year between 2011 and 2018, respectively. At the layer of Levantine Intermediate water the salinity temporal regression reveals a mean trend of 0.010 year −1 . Temperature annual cycle shows an averaged temperature gradient of ∼6 °C in 6 months at the upper layer, with a disconnection with the annual cycle at 100‐m depth. The circulation across the channel is dominated by high‐frequency variability. The signature of eddies with radius ranging from 5 to 18 km is apparent in 16% of the transects analyzed and mainly in spring and summer, with a dominance of subsurface cyclonic eddies. Two‐way flow controls the annual cycle of the water transport through the channel with prevalence of the inflow of Atlantic water. Variations of water transport over timescales of weeks to months can be similar to those identifiable as seasonal changes. Plain Language Summary: Eight years of glider data are used to characterize the temporal and spatial variability of a region in the western Mediterranean that will constitute one of the targets for the calibration phase of the forthcoming Surface Water and Ocean Topography (SWOT) satellite mission. Our results demonstrate that in the Mallorca channel the horizontal dimensions of the scales that SWOT aims to resolve may be as small as 6 km. We observe that the water masses that reside at intermediate layers are increasing their temperature and salinity extrema over time. Temperature annual cycle shows an averaged temperature gradient of ∼6 °C in 6 months at the upper layer, with a disconnection with the annual cycle at 100 m. Dynamic variability at shorter temporal scales is more intense than the annual cycle. Small coherent features are observed in spring and summer, with radius ranging from 5 to 18 km. The transport of water through the channel is characterized by the inflow of recent Atlantic water and the outflow of local Atlantic water. Understanding the hydrodynamics of this region will have an important contribution to the calibration phase of the SWOT satellite mission, the next big breakthrough in Earth observation. Key Points: High‐frequency variability dominates the circulation and transport across the channel The characteristic horizontal dimension of mesoscale instabilities in this region is 6.0 km Two‐way flow controls the annual cycle of the transport of water with prevalence of the inflow of Atlantic water